The Role of Leadership in Encouraging Quality and Performance - Fitrah Amaliah Hasibuan; Nurul Alvi Chindi Fadhilah; Nuriyah; Nurfadlila Amalina (Lembaga Bale Literasi, 2025)
This research discusses the role of leadership in encouraging quality and organizational performance through a quality culture approach and the implementation of Total Quality Management (TQM). Leaders play the role of strategy directors, agents of change, and role models who are able to foster motivation, engagement, and commitment to work in the organization. In the context of TQM, effective leadership requires the ability to build vision, communicate values participalistically, empower employees, and create a culture of continuous improvement. Various leadership styles are explained, such as transformational leadership, servant leadership, to authoritarian leadership, as well as their impact on the success of quality implementation. In addition, quality leadership also plays an important role in building high-performing teams through delegation, coaching, empowerment, and constructive feedback-based performance evaluation. This study shows that leadership is the main foundation in forming an adaptive, collaborative, and quality-oriented work culture so that it can increase organizational productivity and competitiveness